Temporal and spatial fluctuations of sea surface temperature and chlorophyll a levels due to atmospheric forcing in a tropical coastal lagoon - José de Jesús Salas-Pérez; Carlos González-Gándara (Ciencias Marinas, 2016)
The temporal and spatial fluctuations of sea surface temperature (SST) and chlorophyll a (Chla) levels due to atmospheric forcing in Mexico’s third largest tropical coastal lagoon (Tamiahua Lagoon), located in the western Gulf of Mexico, was examined from July 2002 to May 2012. The main hypothesis of this study is that SST and Chla levels are modulated by the exchange of heat fluxes from the atmosphere and by rainfall (river runoff). The atmosphere supplies heat (555.05 ± 42.31 W m–2) to Tamiahua Lagoon, which implies that the temperature of the lagoon over the period analyzed (~27 ºC) was higher than normal in the coastal zone. Precipitation regulates Chla levels during the rainy season because the cross-correlation values were high (r > 0.61) and the phase lag of the rainy season with the Chla time series was typically 0 to –1 month. El Niño/Southern Oscillation phases affected the rainfall patterns and, thus, Chla concentrations in the lagoon. As expected, the lagoon showed eutrophic conditions throughout the year (Chla concentrations >5 mg m–3), with maximum values in the summer, when warm and wet conditions prevail. The annual scale is responsible for most of the variability in the two data sets. Seasonally, both oceanographic data sets showed three different water types, which, in both cases, were more variable at the southern and northern inlets and more homogenous in the central part of the lagoon.